Objectives of the expert consultation - Zerbini, E. (International Livestock Research Institute, 1998)
The principal objective of the workshop was to develop a funding proposal to implement transfer of the IAR/ILRI multi-purpose crossbred cows technologies to eastern African smallholders. The workshop proposed a formal means of co-ordinating and linkage and transfer mechanisms needed to ensure the transfer of the technologies. The secondary purpose of the workshop was to learn from the experiences of experts from countries in Asia where buffalo and cow traction already exists and to discuss the possibility of extending the project of Asia, if additional funding could be found. The occasion of the expert consultation was also used to set up mechanisms for information exchange and collaboration between scientists and development organisations involved in research and transfer of multi-purpose cattle and buffalo technologies in eastern Africa and Asia.